BILINGUALISM AS A FACTOR OF COGNITIVE AND LINGUISTIC DEVELOPMENT OF PERSONALITY - Rano Said-Abdullaevna Makhmadieva,Nasiba Bakhrom kizi Zhalolova (International Journal of Literature and Language Studies, 2026)
Bilingualism is one of the most significant phenomena of the modern world. In the context of globalization, migration, and intercultural communication, the ability to use two or more languages has become increasingly common. Researchers have long been interested in the impact of bilingualism on cognitive processes and language development. This article examines the role of bilingualism in shaping personality, enhancing cognitive abilities, and fostering linguistic competence. The study highlights the advantages of bilingualism in memory, attention, problem-solving, and intercultural communication.